2019
DOI: 10.3390/insects10120439
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Interactions between Insect Biological Control Agents and Semiochemicals

Abstract: Biological control agents and semiochemicals have become essential parts of the integrated pest management of insect pests over recent years, as the incorporation of semiochemicals with natural enemies and entomopathogenic microbials has gained significance. The potential of insect pheromones to attract natural enemies has mainly been established under laboratory conditions, while semiochemicals from plants have been used to attract and retain natural enemies in field conditions using strategies such as trap c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 93 publications
(114 reference statements)
0
26
0
Order By: Relevance
“…Chemical-signaling interactions via BVOCs between plants and plants/insects have biologically important roles in nature (Sharma et al 2019 ). BVOCs are emitted to the atmosphere from leaves or flowers as scents (Dudareva and Pichersky 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical-signaling interactions via BVOCs between plants and plants/insects have biologically important roles in nature (Sharma et al 2019 ). BVOCs are emitted to the atmosphere from leaves or flowers as scents (Dudareva and Pichersky 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…When high wind speeds are experienced (as is more often the case for parasitoids dispersing above the canopy of a low‐growing field crop), these tiny wasps are passively carried in a downwind direction. In an orchard situation, the boundary layer typically occurs above the tree canopy, allowing parasitoids to actively disperse within the tree canopy and to orient upwind toward attractive volatile odors, whether these emanate from plants or hosts 48 . In order to maximize biological control efficacy of G. molesta with Trichogramma dendrolimi , releases should probably be avoided during inclement weather or windy conditions that could potentially interfere with active orientation to hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Through EAG and olfactory bioassay, we confirmed that diethyl sebacate, 1‐octen‐3‐one, and 2,4,4‐trimethyl‐2‐pentene are potential attractants for A. bambawalei . Using insect pheromones and kairomonal semiochemicals from plants to manipulate the behavior of parasitoids and promote their participation as biological control agents have become essential parts of pest management programs 56 . An analogous compound of mealybug pheromone, cyclolavandulyl butyrate, can recruit natural enemies that attack Japanese mealybug, Planococcus kraunhiae under natural conditions 57 .…”
Section: Discussionmentioning
confidence: 99%